2012
DOI: 10.1017/s0033291712001316
|View full text |Cite
|
Sign up to set email alerts
|

The association between social stress and global cognitive function in a population-based study: the European Prospective Investigation into Cancer (EPIC)-Norfolk study

Abstract: In this generally high-functioning population, individuals' interpretations and responses to stressful events, rather than the events themselves, were associated with cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Wilson et al [54] followed a large population based cohort for 5-12 years and found that chronic psychological stress was significantly associated with increased cognitive decline in old age. Authors of another large population based cohort reported that stress was significantly associated with worse global cognitive function over a time period of 10 years [55]. Similarly, authors of two longitudinal studies reported significant correlations for adult participants with higher depression and worse executive function [56,57].…”
Section: Discussionmentioning
confidence: 95%
“…Wilson et al [54] followed a large population based cohort for 5-12 years and found that chronic psychological stress was significantly associated with increased cognitive decline in old age. Authors of another large population based cohort reported that stress was significantly associated with worse global cognitive function over a time period of 10 years [55]. Similarly, authors of two longitudinal studies reported significant correlations for adult participants with higher depression and worse executive function [56,57].…”
Section: Discussionmentioning
confidence: 95%
“…To the authors' knowledge, no other study to date has demonstrated an association between a change in perceived stress as measured by the PSS and change in cognition among older adults. Previous work has shown that perceived stress measured at baseline affects the rate of change of cognition over 7 years (Aggarwal et al, ) and that estimates of previous stress are associated with poorer cognition (Leng et al, ) or incident dementia (Johansson et al, ). A recent study showed that over 2‐year cognitive slowing was related to the overall level of stress reported at six time points (Munoz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of stress perception to age‐related decline has been investigated in few studies and often limited to a single measure of stress, but still, they highlight its unique contribution to the trajectory of cognitive performance. Indeed, in older adults, the retrospective reporting of chronic stress appears to be a better predictor of global cognitive decline than the occurrence of life events (Leng et al, ; VonDras, Powless, Olson, Wheeler, & Snudden, ). Higher baseline perceived stress has also been found to be associated with poorer cognition and a greater rate of decline in a population sample of older adults over 65 (Aggarwal et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In China, similar cultural norms were observed with women doing the majority of domestic work [20]. Shifting domestic roles in cooking from women to men against the social norm might result in men’s experience of psychosocial stress and adverse health outcomes [4, 21, 22]. However, socio-economic status might influence men’s or women’s attitudes towards cooking, thus generating different outcomes [19, 23].…”
Section: Introductionmentioning
confidence: 99%